Serum homocysteine, vitamin B12 and folate levels in healthy Turkish Van Cats - Özkan, Cumali; Kozat, Suleyman; Kaya, Abdullah; Akgul, Yakup (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The present study was conducted for the purpose of setting forth the normal serum Hcy, vitamin B12 and folate levels in Van cats of varying ages and genders, and the age-dependent variations of these parameters. Materials and methods: The material of the study consisted of a total of 60 healthy Van cats including 30 female and 30 male cats. Cats from both genders were separated into 3 groups on the basis of their ages. While the cats of 6 - 12 months of age were included in the first group, cats of 12-24 months of age were included in the second and those of more than 24 months of age were included in the third group. Results: From the blood samples collected; serum normal homocysteine, vitamin B12 and folate levels were determined as 7.1±2.2 nmol/mL, 850.7±231.8 pg/mL and 16.7±0.8 ng/mL, respectively. In the statistical comparison of the determined serum homocysteine, vitamin B12 and folate levels; some variations among different groups of age and genders were determined. However, none of these differences were determined to be statistically significant. Conclusion: The normal levels of serum Hcy, vitamin B12 and folate of healthy Van cats were set forth for the first time by the present study. It is believed that the normal values of these parameters in Van cats can be used in the diagnosis and prognosis of various diseases and particularly cardiovascular diseases, that they will be helpful for researchers and will serve as a guideline to the studies to be conducted in the future. http://doi.org/10.5455/javar.2017.d191